Analisis Strategi Adaptasi Dalam Pemenuhan Kebutuhan Rumah Tangga : (Kasus Pulau Bajo Medang Kecamatan Labuan Badas Sumbawa) - Syarifuddin, Syarifuddin; Rosyadi, Mohammad Arwan; Nurhayati, Nurhayati; Fahrezi, Muhammad A. (Prodi Sosiologi Universitas Mataram, 2024)
This study explores adaptation strategies in fulfilling the household needs of fishing families on Bajo Medang Island, Sumbawa. Bajo Medang Island is mostly inhabited by the Bajo tribe who depend on fishing for their livelihood. Fishermen on Bajo Medang Island depend on natural conditions, namely the fishing season and the lean season. This season affects the catch obtained. In the fishing season the fishermen are busy at sea, on the other hand, in the lean season fishing activities are reduced so that many fishermen are forced to be unemployed. The measurement variables include; household income, allocation of household needs and adaptation strategies carried out by household members. The purpose of the study was to find out (1) How much household income, and use it for what needs. (2) How is the community's adaptation strategy in fulfilling household needs? The research used a descriptive-exploratory quantitative method, determining the sample; the community was determined by quota sampling (rationed), namely 50 households, (10.14%) of the total population of 493 RT. While the sample was selected by stratified proportional random sampling; semi-modern (40%) and traditional (60%) fishermen. The data collection was conducted with structured interviews using questionnaires, observation and documentation. The results showed that most (73.67%) of the fishermen's household income was allocated for basic needs, while the allocation for secondary needs was 18.85% and the allocation for tertiary needs was 7.48%. The community's adaptation strategy in meeting household needs is borrowing from family and or neighbors (52%). This is done because it is easier to meet and has a close emotional relationship. While those who increase the time allocation for the main job are only 48%. This is because the timing of fishing activities depends on natural/climatic conditions.